2016
DOI: 10.1161/hypertensionaha.115.06530
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycorticosterone Acetate/Salt–Induced Cardiac But Not Renal Injury Is Mediated By Endothelial Mineralocorticoid Receptors Independently From Blood Pressure

Abstract: Abstract-Chronic kidney disease has a tremendously increasing prevalence and requires novel therapeutic approaches.Mineralocorticoid receptor (MR) antagonists have proven highly beneficial in the therapy of cardiac disease. The cellular and molecular events leading to cardiac inflammation and remodeling are proposed to be similar to those mediating renal injury. Thus, this study was designed to evaluate and directly compare the effect of MR deletion in endothelial cells on cardiac and renal injury in a model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…63 Endothelial MR is essential in the development of not only endothelial dysfunction and hypertension but in mediating hypertensive cardiac injury and dysfunction. 64,65 These phenomena suggest that MR blockade may provide a key strategy to delay and prevent features of cardiovascular aging. Even low, subpressor doses of the MR antagonist, spironolactone prevented aortic and femoral artery stiffening in female mice fed a high-fat/high-sugar western diet, 66 which is particularly important taking into account that vascular stiffening is the main feature of vascular aging.…”
Section: Mineralocorticoid Receptors In the Regulation Of Oxidative Smentioning
confidence: 99%
“…63 Endothelial MR is essential in the development of not only endothelial dysfunction and hypertension but in mediating hypertensive cardiac injury and dysfunction. 64,65 These phenomena suggest that MR blockade may provide a key strategy to delay and prevent features of cardiovascular aging. Even low, subpressor doses of the MR antagonist, spironolactone prevented aortic and femoral artery stiffening in female mice fed a high-fat/high-sugar western diet, 66 which is particularly important taking into account that vascular stiffening is the main feature of vascular aging.…”
Section: Mineralocorticoid Receptors In the Regulation Of Oxidative Smentioning
confidence: 99%
“…Accordingly, EC-MRKO prevented adverse cardiac remodeling in response to mineralocorticoid/salt-induced hypertension in mice. 26,27 This was associated with a downregulation of intercellular cell adhesion molecule or vascular cell adhesion molecule in MR-deficient endothelial cells and less macrophage infiltration of the heart. 26,27 EC-MRKO 4 or treatment with spironolactone 34 protected from high-fat diet-induced macrophage accumulation, oxidative stress, cardiac fibrosis, and diastolic dysfunction.…”
Section: Inflammation and Novel Mr Targets In Cardiovascular Remodelingmentioning
confidence: 99%
“…24 In contrast, MR deletion from endothelial cells (EC-MRKO) did not alter blood pressure at baseline or in response to mineralocorticoid, mineralocorticoid/salt, or angiotensin II stimulation. 25,26 Vascular relaxation at baseline or after aldosterone treatment was unaltered in mesenteric arteries from MR-deficient mice 25,27 but improved in coronary 25 or aortic 6,27 sections. Obesity and enhanced leptin signaling increased plasma aldosterone levels by 2-to 3-fold in mice.…”
Section: Vascular Stiffness Dysfunction and Blood Pressure Regulationmentioning
confidence: 99%
“…Studies have shown that deficiency of endothelial MR has no effect on renal injury induced by DOC acetate/salt (Lother et al, 2016) and deficiency of podocyte MR has no effect on the development of anti-glomerular basement membrane (anti-GBM) glomerulonephritis (Huang et al, 2014). In contrast, deficiency of MR in smooth muscle cells has recently been shown to limit ischemia-reperfusion injury in the kidney through effects on Rac1-mediated MR signaling (Barrera-Chimal et al, 2017).…”
Section: Mr Signaling In Kidney Fibrosismentioning
confidence: 99%